Sanitasi dan Kebersihan di Kampus UIN Sumatera Utara Medan - P Pagar (Universitas Islam Negeri Sumatera Utara, 2018)
This paper aims to determine the state of sanitation in campus of UIN-SU Medan, then to find out the obstacles in sanitation and hygiene in Medan UIN-SU and to know the steps to improve sanitation and hospitality at UIN SU Medan. The research method uses field research, using sources of data collection from the field as primary data and in the form of literature obtained through the library as secondary data, then using qualitative data analysis methods, and inductive and deductive conclusions. The conclusion of this study is that improvement in sanitation and cleanliness in the UIN-SU Medan in the future requires the following things; 1) Increase sanitation and sanitation personnel, 2) Increase awareness, especially students, as well as the academic community in general, 3) Synchronize lecture time with opportunity for cleaning, 4) Adding clean water supply, 5) Functionalization and addition of room facilities (WC), 6) Working together between the Bureau and the Uini-unit by making an adequate check and balanching system, 7) It is expected that the attention of higher leaders in the future.